Predictive and prognostic value of left ventricular mechanical dyssynchrony assessed by myocardial perfusion single photon emission computed tomography in asymptomatic patients under hemodialysis. Issue 5 (May 2018) - Caobelli, Federico; Popescu, Cristina E.; Laudicella, Riccardo; Comis, Alessio; Pignata, Salvatore A.; Sara, Roberto; Rossetti, Claudio
Abstract : Background: Patients under hemodialysis (HD) have an increased risk of major adverse cardiac events (MACEs). In these patients, myocardial perfusion scintigraphy (MPS) provides useful prognostic information. Left ventricular mechanical dyssynchrony (LVD) has been proven to predict all-cause death in patients under HD. It remains unclear, whether the same prognostic value pertains also to the prediction of MACEs. Patients and methods: Ninety patients under HD (duration range: 2–216 months) with neither history nor symptoms of coronary artery disease at the time of MPS were retrospectively evaluated. All underwent clinical evaluation and MPS with dipyridamole stress test. MPS was reprocessed to derive left ventricular ejection fraction (EF), perfusion scores [summed stress score (SSS) and summed difference score (SDS)] and LVD (phase histogram bandwidth and phase SD). Results MACEs were reported in 10 (11.1%) patients as assessed at more than 2 years of follow-up (median 29 months). At univariate analysis, a correlation was demonstrated between MACEs and LVD ( P <0.001), BMI ( P =0.04), ECG changes during stress ( P =0.03), dyspnea ( P =0.02), SSS ( P =0.04) and SDS ( P =0.02). At stepwise multivariate analysis, only LVD ( P <0.001), SSS ( P =0.01) and SDS ( P =0.001) were independent predictors of MACEs. No thresholds of SSS or SDS showed predictive value ( P =0.79 for SSS ≥4, P =0.10 for SSS >8 and P =0.66 for SDS ≥2). At survival analysis, patients with LVD had a significantly shorter MACE-free survival ( P <0.001). This predictive value held true even in patients with an unremarkable pattern of perfusion. Conclusion: In asymptomatic patients without known coronary artery disease under HD, LVD is highly predictive of the onset of MACEs at more than 2 years of follow-up and provides incremental value over perfusion scores alone. A phase analysis on gated MPS should be routinely performed in these patients to yield useful prognostic information.